Pengaruh Fraud Diamond Terhadap Penyimpangan Akuntansi - Salsabiila Zaeninaa; Arief Himmawan Dwi Nugroho (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the relationship between pressure, opportunity, rationalization and capability on accounting irregularities. This study uses the panel data method and sampling technique with purposive sampling method using manufacturing companies in the basic and chemical sectors in the 2017-2019 period. The results obtained from this study are the influence of financial targets on accounting irregularities and the absence of the influence of financial stability, nature of industry opportunity, rationalization of accounting irregularities